Outcome of tibial shaft fractures treated with the SIGN FIN nail at Addis Ababa Emergency, Burn, and Trauma Hospital (AaEBT) Addis Ababa, Ethiopia - Cheru Beyene Tesso, MD; Lewis G. Zirkle, MD; Abiy Worku, MD; Getachew Tilahun, MPH; Samuel Kebede, MD; Tilahun Desta, MD (OTA International, 2023)
Abstract. Objectives:. To determine the outcome of tibial fractures treated with the SIGN FIN nail. Study Design:. Retrospective case series study. Study Setting:. Trauma center. Methods and Materials:. We included 14 patients aged 18–51 years with 16 tibial fractures in this study. Patients were followed clinically and radiographically, and the minimum time followed was 6 months. Johner and Wruhs criteria with modification were used to assess the outcome. Result:. There were 11 male (78.6%) and three female (21.4%) patients. The mean age was 32.44 ± 8.98 (range 18–51) years. The right-sided tibia was injured in six as compared with the left side in four, and four patients had bilateral injuries. Eight (50%) fractures were closed fractures, whereas the rest eight (50%) were open types of fractures. Among the latter, half (n = 4; 50%) fractures were Gustilo type II fractures, while three (37.5%) fractures were Gustilo type III fractures, and one (12.5%) patient had a Gustilo type I fracture. All patients had radiologic union. There were no infections or secondary surgery for any reason. Excellent, good, and fair results were achieved in 62.5%, 25%, and 12.5%, respectively. All patients were able to return to their preinjury activity except two patients. Conclusion:. SIGN FIN nail is an option for treating tibial shaft fractures with good outcomes and few complications in selected fractures. Level of evidence:. Level IV